Response of Cotton to Varied Levels of Agronomic Management Under High Density Planting System (HDPS) – A Review - S. Jaffar Basha; E. Aruna (International Journal of Economic Plants)
Cotton, a crop of choice, occupies the second premier position next to food crops in providing clothing. Though 53 species of Gossypium are available, only four species are cultivable and among the four, the major cultivable area falls under G. hirsutum. Though varieties with medium, superior medium, long and extra-long staple cotton were released earlier, with the advent of machineries, ginning facilities, mills were literally requiring cotton fiber of any length. With the advent of Bt technology and the release of hybrids during 2002, cotton productivity had gained a momentum. However, considering the duration, cost involved in manual harvesting etc., farmers were looking for alternate option especially under rainfed conditions and High-Density Planting System (HDPS) with compact cotton genotypes is the viable alternative to overcome the stagnant productivity despite following all the suitable agronomic measures like adopting BG II hybrids, maintaining optimum plant population density and following timely plant protection measures. HDPS technology increases the number of bolls per unit area to achieve a high yield, reduces the risk of terminal drought and failure due to pests, gives seed sovereignty to farmers, and is specifically suited for rainfed areas with shallow and medium-deep soils. Under HDPS entries could yield better at 60×10 cm2 spacing under medium depth soils with a planting density of 1.66 lakh plants ha-1. Cotton planted under HDPS need 25% additional fertilizers over the recommendation for varieties.